A MODIFIED SEMANTICS MAPPING STRATEGY BASED ON AN INTERACTIVE APPROACH TO ENHANCE THE STUDENTS' VOCABULARY ACHIEVEMENT - Budiarte, Agus; Setiyadi, Ag. Bambang; Nainggolan, Flora; Sumarta, Ryan Puby (Universitas Muhammadiyah Metro, 2024)
Vocabulary plays an important role in mastering language. Many students have low capability in vocabulary mastery. In this research, the authors aim to improve students' vocabulary mastery by teaching the students through a modified semantics mapping strategy based on an interactive approach. The authors employed quantitative research with an experimental design. The subjects of this research were the second-grade students of SMPN 37 Bandar Lampung. A vocabulary test is used as the instrument of this research. The data were obtained from the pre-test and post-test. Independent group t-test in SPSS was used to analyze the data. The results show a statistically significant difference in vocabulary achievement between the experimental and control classes. It is revealed from the t-value, which is higher than the t-table with a significance level of less than 0.05 (9.865>2.005) (0.000<0.05). As a result, the hypothesis is accepted. This indicates that a modified semantic mapping strategy is better than a semantic mapping strategy in enhancing students' vocabulary achievement. Furthermore, using a modified Semantics Mapping Strategy based on teaching vocabulary is more effective in encouraging students to be involved in teaching-learning activities than using Semantics Mapping Strategy.